2009
DOI: 10.1086/597258
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Severe Disease in Adults with Falciparum Malaria

Abstract: The findings of this study demonstrate that ethnicity and parasitemia are important independent risk factors for severe falciparum malaria in adults from malaria-nonendemic countries and that a history of previous clinical malaria significantly reduces the risk of WHO-defined severe falciparum malaria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
79
5
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(98 citation statements)
references
References 23 publications
10
79
5
4
Order By: Relevance
“…Otros autores consideran que estos criterios son especialmente útiles para estandarizar pacientes que ingresan a ensayos clínicos y que reflejan más criterios de entrada que el resultado de la enfermedad, pero aceptan que muchas de las medidas de gravedad de los criterios de la OMS no son evidentes al ingreso hospitalario, sino que se desarrollan insidiosamente o inesperadamente durante el curso de la enfermedad (25).…”
Section: Complicaciones Clínicas Diagnosticadas Y Criterios Usadosunclassified
See 2 more Smart Citations
“…Otros autores consideran que estos criterios son especialmente útiles para estandarizar pacientes que ingresan a ensayos clínicos y que reflejan más criterios de entrada que el resultado de la enfermedad, pero aceptan que muchas de las medidas de gravedad de los criterios de la OMS no son evidentes al ingreso hospitalario, sino que se desarrollan insidiosamente o inesperadamente durante el curso de la enfermedad (25).…”
Section: Complicaciones Clínicas Diagnosticadas Y Criterios Usadosunclassified
“…Se conocen diferentes valores de recuento de parásitos a partir de los cuales se considera la hiperparasitemia. En infecciones por P. falciparum, la OMS propone un recuento superior a 100.000 o 250.000 parásitos/µl de sangre (2 % o 5 % de eritrocitos parasitados) según la endemia de malaria (3); incluso, para propósitos de investigación se considera como más de 10 % de los eritrocitos parasitados (25). En Colombia, se emplea como criterio un recuento superior a 50.000 formas asexuadas de P. falciparum/µl.…”
Section: Signos Asociados Con Complicación En El Análisis Bivariadounclassified
See 1 more Smart Citation
“…A retrospective study that had been conducted at The University Hospital in Heidelberg, Germany and included 122 patients with falciparum malaria, showed that thrombocytopenia was a significant predictor of severe malaria [21]. These findings were corroborated by other authors [20,38]. In severe malaria, the concentrations of proinflammatory cytokines such as TNF-α, IL-1, IL-6, and IL-12 are elevated [39].…”
Section: Discussionmentioning
confidence: 53%
“…Other authors have found that the proportion of patients with severe disease varies from 1 to 38% of the total number of patients with malaria [17]. Variations in the percentage of patients with the severe form of malaria are best illustrated by the following: the disease was severe in 7.5% of patients with malaria in Canada, in 15.9% in the US and 16% in the UK [18][19][20]. In Germany, 27.9% of patients with malaria caused by P. falciparum had severe disease [21].…”
Section: Discussionmentioning
confidence: 99%